The Depth of Unknowing: Or, How to (Un)Know God according to Pseudo-Dionysius and Raimon Panikkar - Nindyo Sasongko (Asosiasi Teolog Indonesia, 2014)
What is the relevance of the sixth-century writings attributed to Dionysius of Areopagite or Pseudo-Dionysius for twenty-first-century Christianity? This article is an inquiry into the notion of divine unknowability within the Pseudo-Dionysian corpus. As a thinker who lived in an era in which great disputations over cardinal doctrines of the church had become passé, Pseudo-Dionysius seemed to have creatively used different concepts and phrases than those great thinkers before him. For Dionysius, the way to know God is to unknow (agnōsia) God, for God cannot be the object of human knowledge—God is beyond being. To posit God as being or to be existent means, therefore, idolatry, since God is that which cannot be grasped by words or human concepts. To assess this apophatic theology of Pseudo-Dionysius, I shall make use of the thinking of Raimon Panikkar who struggles against Western “strict monotheism.” Finally, I shall demonstrate the implications of the doctrine of the unknowability of God vis-à-vis modern debates on the existence of God and on atheism.